A comparison between ultrasonography and single-phase computed tomography for preoperative assessment of solid abdominal tumors in children - Iara Regina Siqueira Lucena; Márcio Fernandes Chedid; Paola Santis Isolan; Eliziane Emy Takamatu; Ronaldo Albé Lucena; Flavia Heinz Feier; Álvaro Porto Alegre Furtado; Jose Carlos Soares de Fraga (Elsevier, 2023)
Objective: This study aimed to estimate the performance of single-phase-enhanced computed tomography and ultrasonography examinations in the preoperative evaluation of solid abdominal tumors and their relationship with relevant adjacent structures in children. Methods: This retrospective study included 50 pediatric patients with malignant solid abdominal tumors treated with surgical resection between 2009-2017. Preoperative computed tomography and ultrasonography were compared to operative findings (gold standard) in the diagnosis of invasion or encasement of adjacent structures. Accuracy, sensitivity, specificity, and positive and negative predictive values were evaluated. Results: Renal (20.4%) and neuroblastic (19.4%) tumors were the most common. Complete surgical resection with negative margins was achieved in 44 (88%) patients. The comparison between single-phase-enhanced computed tomography and ultrasonography findings showed the following results: sensitivity = 90.3% vs 86.6%, specificity = 86.8% vs 94.6%, negative predictive value = 95.3% vs 94.4%, positive predictive value = 75.3% vs 86.9%, and accuracy = 87.9% vs 92.2%. The correlation (kappa index) between computed tomography and ultrasonography examinations was 0.72 (p < 0.001). In 14% (7/50) of the patients, the invasion of adjacent structures was diagnosed by ultrasonography but not by computed tomography (1 patient had 2 invaded structures). Conclusion: Ultrasonography can be considered a complementary method to single-phase-enhanced computed tomography in the preoperative evaluation of children with an abdominal tumor. The present study showed that ultrasonography and single-phase-enhanced computed tomography each possess a high accuracy in the preoperative planning of resection of solid abdominal tumors in children. Thus, it seems that the combination of both imaging methods would be enough for the evaluation of most abdominal tumors in the pediatric population.